Respect your enemies - The first rule of peace : an essay addressed to the U. S. Anti-war movement - Caffentzis, George (Universidad Nacional de Quilmes, 2003)
There is now a fledgling anti-interventionist, anti-war movement in the US. It will have a lot of work to do in the near future, although the present threat of war on Iraq is the most pressing issue it faces. The question is: can the antiwar movement do its work effectively and successfully? At the moment it is not completely marginalized, if the votes in Congress are any indication. On October 9, between one-quarter to one-third of the congressional representatives voted against granting George W. Bush "war powers." But in order to show itself as expressing the majority perspective in this country, it needs new arguments, a new respect (as in "look again") for its opponents, a deeper understanding of the reasons for the actions of its opponents, and a realistic assessment of their weaknesses. For its old arguments do not seem convincing to the majority of US citizens, and its lack of curiosity about its opponents and their reasoning is dulling its strategic sense.